The efficacy and safety of rhGH treatment combined with letrozole/GnRHa in adolescent boys - Ying Zhang; Xin Yuan; Kenneth McCormick; Xiao-Hong Yang; Shi-Jun Chen; Rui-Min Chen (BMC Pediatrics)
Abstract Objective In boys during puberty who were undergoing recombinant human growth hormone (rhGH) treatment, we compared the therapeutic efficacy on growth, and any adverse reactions, of co-therapy with either letrozole or gonadotropin-releasing hormone analog (GnRHa). Methods Fifty-six pubertal growth hormone deficiency (GHD) boys were studied, they were treated with the combination of letrozole and rhGH (letrozole group, n = 28) or the combination of GnRHa and rhGH (GnRHa group, n = 28) for at least one year. Eighteen patients in the letrozole group and seventeen patients in the GnRHa group attained final adult height (FAH). Results The increase in height of the letrozole group was significantly more than the GnRHa group both in the first year [(10.37 ± 2.19) vs. (7.78 ± 1.55) cm] and at two years [(18.82 ± 2.49) vs. (13.84 ± 2.17) cm] (p < 0.05), however, there was no significant group difference in the advancement of bone age (BA) of in the first year or at two years (p > 0.05). The mean FAH in two groups were similar, but the treatment duration of the letrozole group was significantly less than GnRHa group. There was a significant body mass index (BMI) SDS increase in the letrozole vs. GnRHa groups. Of concern, bone mineral density (BMD) decreased in both groups after treatment, but more so in the letrozole cohort. Conclusion The combination of letrozole/rhGH in pubertal GHD boys was similar to GnRHa/rhGH in terms of the progression of BA and FAH, but the former co-therapy was superior in the gain of height. Disconcertingly, however, this combination may adversely affect BMI and BMD. Clinical trial registration number ChiCTR2300068405.